A Comparative Analysis of the Implementation of Human Resource Management Practices in Public - Mandeep Kumar Berwal, Arun Kumar Agarwal (Mathematical Statistician and Engineering Applications, 2022)
When it comes to the management of human resources, the public sector and private institutions are poles apart from one another in terms of the standards that they uphold in their respective practices. Because of the severe shortage of permanent faculty members, the recruitment of faculty is the top priority at government institutions. This is directly related to the fact that there are not enough permanent faculty members. In government institutions, these are the additional key issues of human resources, in addition to motivation, physical infrastructure, performance assessment of instructors, training, and career trajectories. It is plausible to suggest that human resource issues at government institutions tend to be impacted in a unique way as a result of inadequate resources and bureaucratic delays. On the other hand, the most significant HR challenges faced by private colleges are related to the retention of qualified instructors and the provision of alluring remuneration, both of which are inextricably linked to the high faculty turnover rate that these institutions face. Empowerment and motivation are two additional significant difficulties that come up often in the context of human resources in the commercial sector.